1997
DOI: 10.1093/carcin/18.8.1529
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 (GSTM1) and T1 (GSTT1) polymorphisms and lung cancer risk among Northwestern Mediterraneans

Abstract: Several polymorphic genes including those encoding for glutathione S-transferases (GST) have been reported to be involved in modifying lung cancer risk in smokers. The gene GSTM1 is frequently deleted in humans and a possible association between the null genotype and lung cancer risk is controversial. Another polymorphic gene of the same supergene family, GSTT1, is also involved in the detoxification of some environmental carcinogens. Both genes were genotyped in (a) a group of lung cancer patients (n = 160); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
25
3
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 5 publications
11
25
3
1
Order By: Relevance
“…Results have not supported an association with lung cancer risk (To-Figueras et al, 1997;Malats et al, 2000;Stucker et al, 2002;Ruano-Ravina et al, 2003;Wang et al, 2003b). In bladder cancer, the association is not consistent (Abdel-Rahman et al, 1998).…”
Section: Carcinogen Metabolismmentioning
confidence: 96%
“…Results have not supported an association with lung cancer risk (To-Figueras et al, 1997;Malats et al, 2000;Stucker et al, 2002;Ruano-Ravina et al, 2003;Wang et al, 2003b). In bladder cancer, the association is not consistent (Abdel-Rahman et al, 1998).…”
Section: Carcinogen Metabolismmentioning
confidence: 96%
“…The GSTM1 polymorphism, which is the deletion of the GSTM1 gene leading to the absence of the enzyme, has been reported to be a moderate risk factor for the development of lung cancer (Alexandrie et al, 1994). The GSTT1 polymorphism is also caused by a deletion that results in the total lack of gene product (Alexandrie et al, 2000), deficiency in this enzyme having been correlated with an increased risk of lung cancer (To-Figueras et al, 1997). The GSTP1 polymorphisms GSTP1 (Ile105 Val) and GSTP1 (Ala114 Val) also lead to a decrease in the activity of the corresponding enzyme (Watson et al, 1998), and it has recently been shown that the GSTP1 polymorphism is associated with an increase risk of lung carcinoma (Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[13], [18] Several Caucasian studies were previously conducted to assess the role of GSTT1 in lung cancer susceptibility with the case-control approach. [10], [11], [19][20][21][22] No significant associations of GSTT1 with lung cancer risk could be established, and two of the studies found that the GSTT1 null genotype did not elevate the risk with either lung adenocancer or squamous cell carcinoma. [19], [20] Another study in Chinese found that the GSTT1 genotype was not related to lung cancer.…”
Section: Discussionmentioning
confidence: 99%